Acoustic analysis of the speech of children with cochlear implants and comparison with hearing controls - Mildner, Vesna (Array, 2003)
The aim of this study was to analyze the speech of hearing-impaired children with cochlear implants (CI), and compare it with hearing controls (HC). The following variables were analyzed: vowels (F1 and F2), fricatives /s/ and /sh/ (spectral differences), and affricates /ts/ and /tsh/ (total duration and timing of stop-fricative components). There were 18 elementary-school children in each group, matched for age and sex. Acoustic analysis revealed differences between the two groups in all measured variables. Contrary to expectations, the vowel space spanned by the CI children was not much smaller than that of the HC, the significant difference being along the front-back axis (F2). As expected, fricatives were more clearly separated, with respect to noise frequency, in HC than in the CI group. Most CI children substituted fricatives or stops for affricates, and the total duration of those substitutes was significantly longer than the duration of HC's affricates.